Analisis Pernyataan Standar Akuntasi Zakat PSAK 109 pada Lembaga Amil Zakat Infak dan Sadaqah Muhammadiyah (Lazismu) - Delima Nisa Harahap; Yenni Samri Juliaty Nasution (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2022)
The purpose of this study is determine whether the accounting treatment of zakat in LAZISMU Medan city accordance with PSAK No. 109. This research is conducted to examine the financial statements prepared LAZISMU Medan city and to determine the application zakat, sadaqah and infaq accordance with PSAK No. 109 on Accounting for Zakat. The method used is descriptive approach and this type of data is qualitative. the results of this research concluded that LAZISMU Medan city have not fully implemented use PSAK No.109. in presenting the financial statements. because in PSAK No. 109, zakat accounting aims to regulate the recognition, measurement, presentation and disclosure of transactions zakat, infaq/ Sadaqah.